A new subtype of pachydermodactyly: unilateral pachydermodactyly transgrediens - Nicolay, Jan Peter; Faulhaber, Jörg (Clinical and experimental dermatology, 2015)
Pachydermodactyly describes a rare condition of localized fibromatosis, usually symmetrically affecting the interphalangeal joints of both hands. We describe a case of a new subtype of pachydermodactyly in a 14-year-old boy, which we term ‘unilateral pachydermodactyly transgrediens’. This atypical pattern is caused by specific localized mechanical manipulation of the hands. This condition contributes to the completely indolent spectrum of pachydermodactyly, and usually does not need therapy. Therefore it is essential not to misinterpret it as an inflammatory state such as juvenile idiopathic arthritis. The correct diagnosis of pachydermodactyly and its rare subtypes, as we describe in this case, often spares the affected patients unnecessary invasive diagnostic procedures and immunosuppressive therapy.